THE EFFECT OF ECOTOURISM MOTIVATION AND TRAVEL SATISFACTION ON DESTINATION LOYALTY - Hikmatul Aliyah; Susi Sulastri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The development of ecotourism in various parts of Indonesia is very rapid. However, due to the Covid-19 pandemic, the nature-based tourism business was quickly stopped and the number of visitors decreased. The purpose of this study was to examine and analyze the effect of ecotourism motivation, and travel satisfaction on destination loyalty. The research method uses a quantitative research approach. The population of this study are visitors to the Padang Savana ecotourism object. This research data uses primary data. The data collection technique used a survey by distributing questionnaires to respondents. The data analysis technique used SEM Amos 21 version. The results found that ecotourism motivation had no effect on destination loyalty. However, ecotourism motivation has an effect on travel satisfaction. Other findings that travel satisfaction has no effect on destination loyalty. These findings can be used as a reference for ecotourism business managers to make marketing strategies by increasing ecotourism motivation to increase travel satisfaction. Meanwhile, to increase destination loyalty, managers must look for other more effective strategies. Keywords: Destination Loyalty, Motivation, Travel Satisfaction